Diagnosis of Tuberculous Meningitis by Clinical & Laboratory Parameters - Bharat Lai, Noreen !rum, Ghulam Mustafa Rajput, Tabinda Taqi (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To determine the parameters to diagnose tuberculous meningitis in patients on the bases of clinical and laboratory findings. Methods: This descriptive study was conducted at PMC hospital Nawabshah from Feb 2015 to Feb 2016. 112 patients of suspected meningitis were enrolled by purposive sampling. Physical examinations and baseline diagnostic tests including Cerebro Spinal Fluid analysis, CSF for Acid Fast Bacilli smear, CSF for T.B culture, X-Ray Chest and C.T scan brain with contrast were done and results collected in predesigned questionnare . TB meningitis was diagnosed when CSF mycobacterial culture or AFB stains were positive or clinical meningitis with A: Fever Headache, neck stiffness B: CSF showing increased protein, decrease glucose and lymphocytic predominance pleocytosis C: response to anti tuberculous drugs. Bacterial meningitis was diagnosed by presence of bacteria in CSF by gram staining or culture or clinical meningitis with A: fever headache, neck stiffness B: CSF showing increased protein, decreased glucose, neutrophilic predominant, pleocytosis, C: response to broad spectrum antibiotics, 12 clinical and laboratory features of tuberculous meningitis and bacterial meningitis were compared by univariate and multiple logistic regression analysis. Results: Five parameters were independently predictive of diagnosis of tuberculous meningitis: duration of illness > 7 days, clear CSF appearance, CSF cells < 1000/mm3, CSF lymphocyte > 50%and CSF protein > 100mgidl. When more than 5 parameters are present then sensitivity is 78% and specificity is 63%. Conclusion: Simple clinical and laboratory features can help in diagnosis of tuberculous meningitis. These parameters can help in better management in patients suffering from TB meningitis and in turn will reduce their morbidity and mortality.